Cryptosporidium parvum infection in dairy calves in South Vietnam - Kjellén, Anna (SLU/Dept. of Clinical Sciences (until 231231), 2007)
Infectious diarrhoea of neonatal calves is common worldwide. Several pathogens, e.g. rotavirus and coronavirus, enterotoxigenic Eschericia coli bacteria and the protozoan parasite Cryptosporidium parvum have the potential to cause diarrhoea in calves. In this study, which was part of a larger project on calf diarrhoea in South Vietnam, the occurrence of C. parvum in dairy calves was investigated.